Differential effects of decisional and emotional forgiveness on distress and well-being: A three-wave study of Indonesian adults - Cook, Kaye V.; Kurniati, Ni Made Taganing; Suwartono, Christiany; Widyarini, Nilam; Worthington Jr., Everett L.; Cowden, Richard G. (Frontiers in Psychology, 2022)
Research suggests that interpersonal forgiveness is beneficial to individual functioning, but few longitudinal studies have explored the independent contributions of decisional and emotional forgiveness to reducing different forms of distress and improving multidimensional well-being. In this three-wave (T1: December 2020; T2: January 2021; T3: February 2021) prospective study of predominantly young Indonesian adults (N = 595), we examined the associations of decisional and emotional forgiveness with three indicators of distress and 10 components of well-being. Applying the outcome-wide analytic template for longitudinal designs, our primary analysis involved estimating two sets of linear regression models (one set for decisional forgiveness and one set for emotional forgiveness) in which the outcomes were regressed on each interpersonal forgiveness process (one outcome at a time). Adjusting for a range of covariates (including prior values of decisional forgiveness, emotional forgiveness, and all 13 outcomes) assessed at T1, decisional forgiveness assessed at T2 was associated with an increase in seven components of well-being (i.e., life satisfaction, physical health, sense of purpose, promote good, delayed gratification, content with relationships, satisfying relationships) approximately one month later at T3. In contrast, emotional forgiveness assessed at T2 was associated with an increase in a single component of well-being (i.e., satisfying relationships) assessed at T3. Neither decisional nor emotional forgiveness assessed at T2 showed evidence of associations with any of the subsequent indicators of distress assessed at T3. Our findings suggest that, at least within a principally collectivistic cultural context such as Indonesia, decisional forgiveness in the aftermath of a transgression may have greater short-term benefits for well-being compared to emotional forgiveness. Implications of the findings for research and interventions are discussed.